Veyretia is a new synonym of Cyclopogon (Orchidaceae) - Carvalho, Bruno M.; Baumgratz, José Fernando A.; Meneguzzo, Thiago E. C. (Phytotaxa, 2025)
To solve the paraphyly of Cyclopogon C.Presl the genus Veyretia Szlach. is synonymized with it, and its eleven species are transferred. Of those, a replacement name is given for the former Veyretia aphylla (Ridl.) Szlach. and it is demonstrated the illegitimacy and superfluity of homotypic set of names Sarcoglottis rupicola Garay / Veyretia rupestris Szlach. / Veyretia rupicola (Garay) F.Barros.